Test–Retest Reliability and Responsiveness of PROMIS Sleep Short Forms Within an RCT in Women With Fibromyalgia - Chimenti, Ruth L.; Rakel, Barbara A.; Dailey, Dana L.; Vance, Carol G. T.; Zimmerman, Miriam B.; Geasland, Katharine M.; Williams, Jon M.; Crofford, Leslie J.; Sluka, Kathleen A. (Frontiers in Pain Research, 2021)
Background: Nonrestorative sleep is commonly reported by individuals with fibromyalgia, but there is limited information on the reliability and responsiveness of self-reported sleep measures in this population. Objectives: (1) Examine the reliability and validity of the Patient-Reported Outcomes Measurement Information System (PROMIS) sleep measures in women with fibromyalgia, and (2) Determine the responsiveness of the PROMIS sleep measures to a daily transcutaneous electrical nerve stimulation (TENS) intervention in women with fibromyalgia over 4 weeks compared with other measures of restorative sleep. Methods: In a double-blinded, dual-site clinical trial, 301 women with fibromyalgia were randomly assigned to utilize either Active-TENS, Placebo-TENS, or No-TENS at home. Measures were collected at baseline and after 4 weeks of treatment. To assess self-reported sleep, the participants completed three PROMIS short forms: Sleep Disturbance, Sleep-Related Impairment, Fatigue, and the Pittsburgh Sleep Quality Index (PSQI). To assess device-measured sleep, actigraphy was used to quantify total sleep time, wake after sleep onset, and sleep efficiency. Linear mixed models were used to examine the effects of treatment, time, and treatment*time interactions. Results: The PROMIS short forms had moderate test–retest reliability (ICC 0.62 to 0.71) and high internal consistency (Cronbach's alpha 0.89 to 0.92). The PROMIS sleep measures [mean change over 4 weeks, 95% confidence interval (CI)], Sleep Disturbance: −1.9 (−3.6 to −0.3), Sleep-Related Impairment: −3 (−4.6 to −1.4), and Fatigue: −2.4 (−3.9 to −0.9) were responsive to improvement in restorative sleep and specific to the Active-TENS group but not in the Placebo-TENS [Sleep Disturbance: −1.3 (−3 to 0.3), Sleep-Related Impairment: −1.2 (−2.8 to 0.4), Fatigue: −1.1 (−2.7 to 0.9)] or No-TENS [Sleep Disturbance: −0.1 (−1.6 to 1.5), Sleep-Related Impairment: −0.2 (−1.7 to 1.4), Fatigue: –.3 (−1.8 to 1.2)] groups. The PSQI was responsive but not specific with improvement detected in both the Active-TENS: −0.9 (−1.7 to −0.1) and Placebo-TENS: −0.9 (−1.7 to 0) groups but not in the No-TENS group: −0.3 (−1.1 to 0.5). Actigraphy was not sensitive to any changes in restorative sleep with Active-TENS [Sleep Efficiency: −1 (−2.8 to 0.9), Total Sleep Time: 3.3 (−19.8 to 26.4)]. Conclusion: The PROMIS sleep measures are reliable, valid, and responsive to improvement in restorative sleep in women with fibromyalgia. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT01888640.